If Walls Had Ears = Als muren oren hadden 1984-2005. - Archer, Michael; Bos, Saskia; Esche, Charles; von Graevenitz, Antje; Hanru, Hou; Heiser, Jörg; Jantjes, Gavin; Lambrecht, Luk; Pohlen, Annelie; van Duyn, Edna (Amsterdam : De Appel Foundation Amsterdam, 2005)
Abramovic, Marina ; Absalon ; Adams, Dennis ; Ahtila, Eija-Liisa ; Almarcegui, Lara ; Almond, Darren ; Altena, Maarten ; Alvi, Tariq ; Amer, Ghada ; Amorales, Carlos ; Ang, Tiong ; Antoni, Janine ; Applebroog, Ida ; Araki, Nobuyoshi ; Asher, Dan ; Ashes, Daniel J. ; Auguste-Dormeuil, Renaud ; Bagnoli, Marco ; Bain, Mark ; Baldessari, John ; Balka, Miroslaw ; Banner, Fiona ; Barry, Judith ; Bartana, Yael ; Bartolini, Massimo ; Bastiaans, Christiaan ; Bedaux, Jacoba ; Beeke, Anthon ; Bekirovic, Sema ; Bell, Craig ; Beltrán, Erick ; Benczúr, Emese ; Berchem, Otto ; van Bergen, André ; Bien, Waldo ; Bijl, Guillaume ; Bijl, Marc ; Billingham, Richard ; Birnbaum, Dara ; Blake, John ; Blankestein, Jan ; Blocher, Sylvie ; Bloom, Barbara ; Bond, Henry ; Bonvicini, Monica ; Borland, Christine ; Borofsky, Jonathan ; Boyce, Martin ; Breitz, Candice ; Brinch, Jes ; Brito, Hugo ; Broodthaers, Marcel ; Brown, Tony ; van Brummelen, Lonnie ; Bruys, Nathalie ; Bulatov, Erik ; Bunuel, Luis ; Burki, Marie José ; Burton, Scott ; Bustamante, Jean-Marc ; Cabrita Reis, Pedro ; Cage, John ; Calle, Sophie ; Cantor, Mircea ; Caramelle, Ernst ; Carrión, Ulises ; Cate, Ritsaert ten ; Cattelan, Maurizio ; Chauchat, Alice ; Choi Jeong Hwa ; Choi, Sulki ; Ciraci, Sarah ; De Cock, Jan ; Coenen, Arno ; Collins, Hannah ; de Cordier, Thierry ; Corillon, Patrick ; Cox, Huub ; Cristovao, Claudia ; D'Orazio, Federico ; Daem, Hilde ; Daniels, René ; Davey, Grenville ; Davids, Yael ; Dejanov, Plamen ; Demand, Thomas ; Diesel ; Dietvorst, Jan ; Dion, Mark ; Doherty, Willie ; Dominguez, Juan ; Donachie, Jacqueline ; Dujourie, Lili ; Dumas, Marlene ; Duprat, Hubert ; Eckart, Christian ; Edzgveradze, Gia ; Eisinga, Jeroen ; Eliasson, Olafur ; Emin, Tracey ; Espaliú, Pepe ; Eynaudi, Alix ; etc.
De Appel 1975-2005 Kunstenaars A-Z p. 688--697
Tentoonstellingen & Activiteiten 1984-2005 p. 699-703
Engels
Nederlands
boek